201 Descriptive Case Series of Oncologic Brachial Plexopathy at a Comprehensive Cancer Center. (April 2023) - Lim, Jaims; Moser, Matthew; Popoola, Daniel; Prasad, Dheerendra; Fenstermaker, Robert A.; Fabiano, Andrew J.; Lipinski, Lindsay
Abstract : INTRODUCTION: Primary compression or metastatic spread into the peripheral nervous system is an unfortunate sequela of solid-organ cancers and leads to serious pain and neurologic symptoms. Neoplastic brachial plexopathy is poorly understood and treatments vary based on systemic disease burden and symptoms. METHODS: After IRB approval, a systematic search of the medical record was conducted for patients with brachial plexopathy based on CPT from 2016 to 2020. Patients with direct neural infiltration and/or external compression by primary or metastatic tumor were included. Radiation-induced brachial plexopathy cases were excluded. Data were collected regarding demographics, primary cancer, symptoms, exam, pain management treatments, primary cancer management, and outcomes. RESULTS: A total of 15 patients were identified with either infiltrative or compressive brachial plexopathies. The most common primary cancer was breast. Other types included squamous cell carcinoma of the head and neck, renal cell carcinoma, cholangiocarcinoma, and prostate carcinoma. Patients presented with a diverse array of motor and sensory symptoms including proximal and distal upper extremity weakness, hand spasms, numbness and decreased sensation, paresthesia, and upper extremity swelling. The majority of included patients complained of pain of varying nature. Gabapentin, opioids, and pregabalin were the most common prescribed medications. Overall prognosis in patients with brachial plexus infiltration was poor and less than 1 year. There was little consensus on standardized treatment regimens and management for included patients with plexopathies. CONCLUSIONS: Neoplastic brachial plexopathy is a relatively uncommon, and perhaps underrecognized, pattern of metastatic disease or direct spread in solid organ malignancy and is often associated with severe symptoms and disability. This study highlights need for a multidisciplinary approach including medical oncology, neurosurgery, radiation medicine, pain management, and physical/occupational therapy.